Expected Value Premium Principle Pada Data Reasuransi - Radot Mh Siahaan; Dian Anggraini; Andi Fitriawati; Dani Al Makhya (Unisda Journal of Mathematics and Computer Science (UJMC), 2020)
The amount of stop loss cover reinsurance using krone as Danish currency. The stop loss cover reinsurance scheme with a retention value of r = 50 million krone from fire insurance data in Denmark from 1980-1990 with truncate date at 10 million krone, resulting in a conditional expected value that decreases in value when the higher the threshold value. This is indicated by the threshold value of 1 = 2.976 resulting in pure premium of 1 = 0.1217, a threshold value of 2 = 10.0539 resulting in pure premium 2 = 0.0867 and a threshold value of 3 = 26.199 resulting in pure premium 3 = 0.0849. The use of expected value premium principle with the loading factor () is weighted to the value of the pure premium represented by. This is indicated by the weight of premium 1 = 0.13387, the weight of the premium 2 = 0.09537 and the weight of premium 3 = 0.09339.